PERANGKAT WIRO 1.0 SEBAGAI ALAT BANTU PROSES PENGUMPULAN INFORMASI WIFI - Gigih Supriyatno; Budi Siswanto (Jurnal Ilmiah FIFO, 2018)
Information gathering activities are currently implemented with laptop equipment and external antennas. Such a device may cause suspicion that leads to personnel vulnerabilities in the field. This research will discuss about the design of equipment that is more flexible and small to support information gathering activities of wifi signal analysis by utilizing Rasberry Pi device as a replacement for laptop devices. The research method begins by describing how data retrieval works through wifi, how the Rasberry Pi works and then designing the device and the software system used.This design produces a special wifi signal gathering device pack 4-way handshake that has smaller dimensions, practical, avoid suspicion and able to operate automatically.